Coordinating different representations in the hippocampus - Kelemen, Eduard; Fenton, André A (Neurobiology of learning and memory, 2016)
The processes that organize different thoughts and memories, allowing the separation of currently relevant and irrelevant information, are collectively known as cognitive control. The neuronal mechanisms of these processes can be investigated by place cell ensemble recordings during behaviors and environmental manipulations that present cognitive control challenges to selectively represent one of multiple possible alternative estimates of location. We review place cell studies that investigate responses to manipulations that dissociate the environment into two or more spatial frames of locations, often times to test notions of pattern separation. Manipulations, such as continuously rotating the recording chamber reveal that the ensemble discharge in hippocampus self-organizes into multiple, transiently-organized representations of space, each defined by the subset of coactive cells. Ensemble discharge in the hippocampus alternates between separate representations of frame-specific positions on timescales from 25 ms to several seconds. The dynamic, functional grouping of discharge into transiently co-active subsets of cells is predicted by the animal's changing behavioral needs. In addition to identifying neural correlates of cognitive control in hippocampus, these observations demonstrate that the separation of neuronal activity into distinctive representations depends on ongoing cognitive demands and that what can appear as noise, deviations from receptive field tuning, can substantially be the result of these internal knowledge-guided fluctuations. These findings inspire a new perspective that should be taken into account when investigating pattern separation--a perspective that emphasizes changes in hippocampal neural discharge that are happening on a short timescale and does not assume that patterns of neural discharge are steady and stationary across the several minutes of the recordings.
Keywords: prostorové učení; Rats; krysa rodu Rattus; prostorová paměť; Animals; Models, Neurological; modely neurologické; lidé; hipokampus; vnímání prostoru; Hippocampus; Place Cells; Spatial Memory; Humans; Space Perception; zvířata; buňky místa; Spatial Learning